ANALISIS DETERMINAN KUALITAS PELAPORAN KEUANGAN PERUSAHAAN NON JASA KEUANGAN DI BURSA EFEK INDONESIA - Digdowiseiso, Kumba; Subiyanto, Bambang; Fahlevi Lubis, Reza (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2022)
This study aims to analyze the determinants that affect the quality of financial reporting, which constitutes leverage, company size, cash flow volatility, sales volatility, company operating cycle, loss proportion, intangible asset intensity, and capital intensity. We used the WarpPLS 7.0 program in analyzing the secondary data. The sample in this study were non-financial service companies selected through the purposive sampling technique in the period 2015-2019. The research method used is the descriptive quantitative method with regression analysis. The research results showed that leverage, company size, and capital intensity had a significant and positive effect on the quality of financial reporting. Meanwhile, the operating cycle, the proportion of losses, and the intensity of intangible assets had a significant and negative effect on financial reporting quality. However, cash flow volatility and sales volatility produced an insignificant effect on the quality of financial reporting.